How to Avoid Plagiarism: Student Handbook - Gojná, Zuzana; Kozmanová, Irena; Černikovský, Petr; Vorel, František; Vorlová, Helena; Tesaříková Čermáková, Klára; Holeček, Tomáš; Mach, Jan; Válová, Adriana; Římanová, Radka; Hradecký, Jan; Foltýnek, Tomáš; et al. (Karolinum Press, 2021)
In this handbook you’ll learn: – how to formulate your own ideas – how to correctly reference different sources – what exactly constitutes plagiarism – how to avoid various forms of plagiarism – examples of (in)famous cases of plagiarism – three tips against plagiarism – and finally, some advice for avoiding time pressure.